On the theory of semi-Fredholm operators in topological linear spaces - Vladimirsky, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Н. Владимирский. К теории полуфредгольмовых операторов в топологических линейных пространствахJ. Vladimirskis. Apie pusiau Fredholmo tipo operatorių teoriją tiesinėse topologinėse erdvėse